Carbon Dioxide and Methane Dynamics in a Peatland Headwater Stream: Origins, Processes and Implications. Issue 7 (6th July 2022) - Taillardat, Pierre; Bodmer, Pascal; Deblois, Charles P.; Ponçot, Alex; Prijac, Antonin; Riahi, Khawla; Gandois, Laure; del Giorgio, Paul A.; Bourgault, Marc André; Tremblay, Alain; Garneau, Michelle
Abstract: First‐order streams flowing through peatlands receive, carry and transform large amounts of organic carbon, methane (CH4 ) and carbon dioxide (CO2 ) but remain poorly documented. The objectives of this study were to (a) identify the origins of CO2 and CH4 (thereafter C‐GHG for carbon greenhouse gases) in a peatland headwater stream, (b) determine the environmental factors driving C‐GHG export and emissions, and (c) quantify C‐GHG losses from this system and discuss its implications. Data were collected from eight sampling sites along a 3 km boreal peatland headwater stream (Eastern Canada) over the growing seasons 2019 and 2020. The studied stream was oversaturated in p CO2 [min: 2, 044; max: 23, 306 μatm] and p CH4 [14; 17, 614 μatm]. A mass balance model showed that ∼81% of in‐stream CO2 originated from porewater seepage while the remaining 17% and 2% originated from in‐stream productivity and methane oxidation, respectively. Porewater seepage was concluded to be the primary source of CH4 . Seasonal dissolved C‐GHG concentrations were negatively correlated with the peatland water table depth, suggesting an active release of carbon‐rich peat porewater during the base flow. Nevertheless, greater C‐GHG losses occurred during stormflow periods which acted as pulses with most of the C‐GHG being shunted downstream. The sum of C‐GHG export and emissions at our site was 8.08 gC m −2 y −1 with 86% being released to the atmosphere and 14% being exported downstream. Our study demonstrates that peatland headwater streams act as large sources of C‐GHG and that precipitation events and topography control the magnitude of the fluxes. Plain Language Summary: Headwater streams are the inceptive fragment of the river network where a substantial quantity of organic carbon is released from the surrounding substrate. This terrestrial organic carbon can also be transformed into greenhouse gases (GHGs) such as methane and carbon dioxide. In the stream, those GHG can be either consumed, emitted to the atmosphere, or exported downstream. However, the respective contribution of those pathways is unknown. We sampled a stream draining a rain‐fed peatland in Eastern Canada to describe and quantify its carbon GHG dynamics. We found higher concentrations in this stream than in most headwater streams but the total carbon emissions and export were comparable. Peatland streams typically have a low velocity and gentle slope which minimizes atmospheric gas release. We also found that concentrations were greater during the low flow period, potentially because carbon‐rich porewater was released from the peat. However, greater export was reported during the few days of intense rain. The significance of this work is that GHG in headwater streams are spatially and temporally variable and controlled by the surrounding ecosystems, the intensity of rain events and the stream morphology. The inclusion of this variability will improve regional and global carbon budget estimates. Key Points: Porewater seepage accounted for 81% of the carbon dioxide (CO2 ) present in the stream, in‐stream production and methane (CH4 ) oxidation contributed to 17% and 2% 86.5% of the dissolved CO2 and CH4 was emitted to the atmosphere rather than exported downstream due to gases oversaturation and slow flow 46% of the CO2 and CH4 exported downstream occurred during the 10% period when water discharge rates were maximum, suggesting a pulse effect